2007
DOI: 10.1177/1059601106291114
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond Gender to Discover Differences in Sensitivity to Disempowering Acts

Abstract: The purpose of this study is to examine levels of perceived offensiveness based on observations of disempowering acts and to identify any differences in perceptions based on gender, ethnicity, and a social context in which respondents held majority versus minority status. Gender emerged as a strong determinant of differences in levels of perceived offensiveness, with women reporting higher levels of perceived offensiveness when viewing disempowering acts than did men. However, when comparing groups of the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…While empowerment has been found to be an important contributor to workplace effectiveness (Spreitzer, 2008), there seems to be a bit more to the story. Research on workplace gender and gender discrimination, suggests that employees can also be disempowered (e.g., Eylon & Bamberger, 2000, Vance, Ensher, Hendricks, & Harris, 2004Young, Vance, & Harris, 2007). Disempowering behavior is not the absence of the aforementioned empowering acts.…”
Section: Page 45 Of 107mentioning
confidence: 99%
See 1 more Smart Citation
“…While empowerment has been found to be an important contributor to workplace effectiveness (Spreitzer, 2008), there seems to be a bit more to the story. Research on workplace gender and gender discrimination, suggests that employees can also be disempowered (e.g., Eylon & Bamberger, 2000, Vance, Ensher, Hendricks, & Harris, 2004Young, Vance, & Harris, 2007). Disempowering behavior is not the absence of the aforementioned empowering acts.…”
Section: Page 45 Of 107mentioning
confidence: 99%
“…When supervisors engage in disempowering behaviors, they decrease their subordinates' sense of self-efficacy, self-confidence, psychological control, and influence within their work roles (i.e., diminishing their subordinates' empowerment cognitions) (Vance et al, 2004;Young et al, 2003;Young et al, 2007). Thus, as empowering acts increase the empowerment cognitions of subordinates, disempowering acts have an opposing impact.…”
Section: Page 46 Of 107 Academy Of Management Annalsmentioning
confidence: 99%
“…Control variables. Prior studies have indicated that women experience greater incivility from other women than from men (Gabriel et al, 2018), and women are more sensitive to uncivil acts (Young et al, 2007). Therefore, employee and leader gender (0 5 Female, 1 5 Male) were controlled in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…As ethnicity is one of the strongest determinants of one's social identity (Deaux, Reid, Mizrahi & Ethier, 1995;Young, Vance, & Harris, 2007), we anticipate that ethnic identity will contribute to perceptions of stereotype threat. How ethnic identity contributes to stereotype threat is up for debate, however.…”
Section: A Model Of Stereotype Threat In An Applied Settingmentioning
confidence: 99%